The Philosophy of Laugh and Humor in the Modern Historical-philosophical Discourse - Stoliar, Maryna (Sententiae, 2018)
Rewiev of Amir, L. (2014). Humor and the Good Life in Modern Philosophy: Shaftesbury, Hamann, Kierkegaard. Albany: State University of New York Press.